2020
DOI: 10.4025/jphyseduc.v31i1.3137
|View full text |Cite
|
Sign up to set email alerts
|

High school students’ academic performance associated with psychological aspects, body practices and physical activity

Abstract: The objective of this study was to verify the association of psychological factors and body practices with the academic performance of high school students. A sample of 330 students participated, made up of 167 girls and 163 boys. Likert scale instruments were used for collecting information on self-concept, and on general and academic self-efficacy. Time spent on moderate to vigorous physical activity was recorded, and so was participation in several types of body practices, such as sports, dances, martial ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Further studies can contribute to enriching evidence-based literature, serving as an informative source regarding the prospective design of educational environments that are most appropriate for the development of effective metacognitive skills and self-efficacy, assuming that the key roles of metacognition and self-efficacy are supported therein [21]. Guilherme and Aline suggested that schools should seek alternatives to improve the academic performance of high school students, beyond the traditional development of theoretical-scientific teaching, using methodologies that favor psychological attributes related to self-perception, such as self-concept and self-efficacy [12]. An intervention program could be developed and implemented that improves the mathematics interactions between parents and their children [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies can contribute to enriching evidence-based literature, serving as an informative source regarding the prospective design of educational environments that are most appropriate for the development of effective metacognitive skills and self-efficacy, assuming that the key roles of metacognition and self-efficacy are supported therein [21]. Guilherme and Aline suggested that schools should seek alternatives to improve the academic performance of high school students, beyond the traditional development of theoretical-scientific teaching, using methodologies that favor psychological attributes related to self-perception, such as self-concept and self-efficacy [12]. An intervention program could be developed and implemented that improves the mathematics interactions between parents and their children [17].…”
Section: Discussionmentioning
confidence: 99%
“…Guilherme and Aline used linear regression analysis to verify the association of independent variables (self-concept, perceived General Self-Efficacy Scale, the academic self-efficacy Scale in math) with academic performance and the sample included 330 students 14 to 17 years old in high school/technical courses [12]. Ya-Ling and Jyh-Chong identified Taiwanese junior-high school students' mathematics learning profiles and their roles in mathematics learning self-efficacy and academic performance by using CFA analysis of the COLM Questionnaire [13].…”
Section: In the Field Of Mathematics Self-efficacy Directly Relating ...mentioning
confidence: 99%
“…It is a multidimensional, complex, and specific construct and there are different ways of defining and assessing it. Traditionally, the more objective, quantitative branch assumes academic performance (classifications, number of years to finish the course) as a primordial element in this investigation, and for a long time it was observed as a synonym for success (Araújo, 2017;Ferrão & Almeida, 2019;Gasparotto, Bichels, Szeremeta, Vagetti, & Oliveira, 2020;Soares & Almeida, 2019). It is important to emphasize that its assessment is made by means of classifications in each curricular component and together they make up an average score of grades per term or academic year, which will serve the purpose of reference for approval or failure of students.…”
Section: Introductionmentioning
confidence: 99%
“…O sucesso acadêmico, nesse contexto, pode ser compreendido sob ótica quantitativa e qualitativa, sendo um constructo multidimensional, complexo e específico, existindo assim diversas maneiras de o definir e avaliar. Tradicionalmente, a vertente quantitativa, mais objetiva, assume o desempenho acadêmico (classificações, número de anos para concluir o curso) como elemento primordial nessa investigação, sendo por muito tempo observado como sinônimo de sucesso (Araújo, 2017;Gasparotto, Bichels, Szeremeta, Vagetti, & Oliveira, 2020;Ferrão & Almeida, 2019;Soares & Almeida, 2019). A sua avaliação é feita, destacadamente, tomando as classificações em cada componente curricular que juntos formam um escore médio de notas por período ou ano letivo, que servirá como referência para aprovação ou reprovação dos estudantes.…”
unclassified